Examining identity disclosure: Racial and ethnic identity amongst Multiracial/ethnic adults in the United States - Jaimie Shaff; Janel Cubbage; Sachini Bandara; Holly C. Wilcox (Wiley, 2024)
Abstract Objectives Providing personal demographic information is routine practice in the United States, and yet, little is known about the impacts of this process. This study aims to examine the experiences and perspectives of Multiracial/ethnic adults in the United States when disclosing racial/ethnic identity. Methods Seventeen semistructured interviews were conducted with adults identifying as Multiracial/ethnic. The Multiracial/ethnic identities of participants included Black or African American and White; Black or African American, American Indian or Alaska Native (AI/AN) and Hispanic or Latino; Black or African American and Hispanic or Latino; Black or African American and AI/AN; AI/AN and White and Asian, Native Hawaiian or Pacific Islander and White. Multiple participants reported identifying with multiple ethnic groups for any single broad category. Three identified as sexual minorities. Nine were Millennials; six were Gen X; one was Gen Z; one was Baby Boomer. Qualitative data were analyzed using staged hybrid inductive-deductive thematic analysis. Results Disclosure of racial and ethnic identities presents a unique stressor for Multiracial/ethnic populations due to methods used to obtain data, perceived mismatch of identity and phenotype and exposure to prejudice. Social norms, constructs and movements impact the categories that a Multiracial/ethnic person indicates to external parties. Conclusions The stress and negative feelings that Multiracial/ethnic adults face when identifying their race/ethnicity underscore the broader implications of standard demographic questions on feelings of inclusivity and visibility within a population. Patient or Public Contribution Gathering data on individuals' racial and ethnic backgrounds is a standard practice, and yet, it can pose challenges for those who identify with multiple groups or do not see their identities reflected in the options provided. Such individuals may feel excluded or experience unfair treatment when disclosing their identity, leading to significant stress. As the frequency of this data collection increases, it is essential that the questions are posed empathetically and equitably, with a strong commitment to enhancing inclusivity throughout the process.